2018
DOI: 10.3389/fpsyg.2018.01562
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Local and Global Ordering Strategies in Number Line Estimation in Early Childhood

Abstract: A lot of research has been devoted to number line estimation in primary school. However, less is known about the early onset of number line estimation before children enter formal education. We propose that ordering strategies are building blocks of number line estimation in early childhood. In a longitudinal study, children completed a non-symbolic number line estimation task at age 3.5 and 5 years. Two ordering strategies were identified based on the children’s estimation patterns: local and global ordering.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, a general association between quantity and space is not sufficient for correct positioning of quantities on a number line. Previous research has shown that children use various ordering strategies on a non-symbolic number line estimation task (Kim & Opfer, 2018;Van 't Noordende et al, 2018). A crucial aspect of number line estimation strategies is understanding the order of quantities and the distance between quantities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a general association between quantity and space is not sufficient for correct positioning of quantities on a number line. Previous research has shown that children use various ordering strategies on a non-symbolic number line estimation task (Kim & Opfer, 2018;Van 't Noordende et al, 2018). A crucial aspect of number line estimation strategies is understanding the order of quantities and the distance between quantities.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial aspect of number line estimation strategies is understanding the order of quantities and the distance between quantities. The development of these strategies probably relies on both ordinality and cardinality aspects ( Van 't Noordende et al, 2018). This shows that further refinement of the general magnitude system is necessary to develop early numerical cognition, which is probably enhanced through experience with both quantities and numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Others, however, argue that a bilinear representation is at least as accurate an account for this shift (Dackermann et al, 2015;Ebersbach et al, 2008). Successful number line estimation draws on an understanding of ordinality ( Van 't Noordende et al, 2018) and the use of reference points (Sullivan & Barner, 2014a). The latter, particularly the midpoint, not only facilitates estimation but encourages the development of proportional reasoning (Bicknell & Young-Loveridge, 2015;Rouder & Geary, 2014).…”
Section: Number Line Estimationmentioning
confidence: 99%
“…Number line estimation entails "translating a number into a spatial position on a number line" or, less commonly, "translating a spatial position on a number line into a number" (Siegler, Thompson, Opfer, 2009, p. 144). Successful number line estimation draws on an understanding of ordinality ( Van't Noordende et al, 2018) and the use of reference points (Sullivan & Barner, 2014). In many respects, despite having limited real-world relevance, its impact on mathematics learning is profound.…”
Section: Introductionmentioning
confidence: 99%